The use of anakinra in the treatment of secondary hemophagocytic lymphohistiocytosis. Issue 11 (29th July 2020) - Bami, Sakshi; Vagrecha, Anshul; Soberman, Danielle; Badawi, Mohamad; Cannone, Daniel; Lipton, Jeffrey M.; Cron, Randy Q.; Levy, Carolyn Fein
Abstract: Background: Hemophagocytic lymphohistiocytosis (HLH) can be familial or secondary, which is often triggered by infection or malignancy. HLH therapy includes dexamethasone and etoposide. However, therapy is associated with significant morbidity and mortality. Anakinra, a recombinant interleukin‐1 receptor antagonist, has been reported to treat macrophage activation syndrome (MAS), rheumatic sHLH. We report our experience with anakinra to treat patients with nonrheumatic secondary HLH (sHLH). Procedure: Six children were diagnosed with HLH from December 2014 to August 2016 and were treated with subcutaneous anakinra (6‐10 mg/kg/day divided over four doses) with or without dexamethasone (10 mg/m 2 /day). Therapy was either escalated or weaned based on clinical and laboratory response. Results: Five of six patients were treated with anakinra and dexamethasone, and one with anakinra alone due to active cytomegalovirus (CMV) pneumonitis. The median age of diagnosis was 1.8 years (range 0.8‐14.9 years). No pathogenic mutations associated with HLH were identified, but three of six possessed genetic variants of unknown significance. Infectious triggers were identified for four patients and two patients had malignancies. The average treatment duration was 8 weeks with 3.5‐5.5 years of follow up. No patient needed escalation of therapy to include etoposide. All patients achieved remission. Anakinra was well tolerated without significant adverse effects. Conclusion: Initial treatment with anakinra (with or without dexamethasone) is a feasible treatment alternative for patients with secondary HLH and may allow for avoidance of etoposide. We recommend early initiation of anakinra when HLH is suspected. A broader investigation of the use of anakinra as a first‐line agent for HLH is ongoing.